1990
DOI: 10.1073/pnas.87.16.6470
|View full text |Cite
|
Sign up to set email alerts
|

1 alpha,25-dihydroxyvitamin D3 regulates the expression of carbonic anhydrase II in nonerythroid avian bone marrow cells.

Abstract: la,25-Dihydroxyvitamin D3 [1,25(OH)2D3], the active metabolite of the steroid hormone vitamin D, is a potent regulator of macrophage and osteoclast differentiation. The mature osteoclast, unlike the circulating monocyte or the tissue macrophage, expresses high levels of carbonic anhydrase H (CAH). This enzyme generates protons and bicarbonate from water and carbon dioxide and is involved in bone resorption and acid-base regulation. To test whether 1,25(OH)2D3 could induce the differentiation of myelomonocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…Although our results do not address the issue of pp60~-'~'s functional role in bone resorption, they indicate that the protein is specifically expressed at high levels in the osteoclast, as shown by immunocytochemistry, immunoblotting, and src kinase activity. Induction of differentiation of bone marrow mononuclear cells toward an osteoclast-like phenotype by treatment with 1,25(OH):D3 (4,5,33) led to higher levels of pp60 ~ .... than in untreated cells, further suggesting that osteoclasts are characterized by elevated c-src expression. These results clearly demonstrate a direct link between the osteoclast and c-src expression, and strongly suggest, but by no means prove, that the osteoclast may be the site of the specific defect in c-src-mice that leads to impaired osteoclast function and osteopetrosis.…”
Section: Discussionmentioning
confidence: 87%
“…Although our results do not address the issue of pp60~-'~'s functional role in bone resorption, they indicate that the protein is specifically expressed at high levels in the osteoclast, as shown by immunocytochemistry, immunoblotting, and src kinase activity. Induction of differentiation of bone marrow mononuclear cells toward an osteoclast-like phenotype by treatment with 1,25(OH):D3 (4,5,33) led to higher levels of pp60 ~ .... than in untreated cells, further suggesting that osteoclasts are characterized by elevated c-src expression. These results clearly demonstrate a direct link between the osteoclast and c-src expression, and strongly suggest, but by no means prove, that the osteoclast may be the site of the specific defect in c-src-mice that leads to impaired osteoclast function and osteopetrosis.…”
Section: Discussionmentioning
confidence: 87%
“…Preliminary evidence indeed suggests that the CAII gene is regulated by retinoic acid in normal bone marrow progenitors (C. Schr6der and H. Beug,unpubl.). Other studies have demonstrated that CAII is also regulated by T3, vitamin D3, and androgen (Harkonen and V/i/in~inen 1988;Hillstrom-Shapiro et al 1989;Billecocq et al 1990;Pain et al 1990). However, no cis-acting hormoneresponse element has been identified thus far in the regulatory region of the CAII gene.…”
Section: Discussionmentioning
confidence: 99%
“…The calculated HCO 3 − output from the ABL5 was used as a measure of proper humidification. Assuming that BMPCs cells do not produce their own bicarbonate through carbonic anhydrase [23], increases or decreases in HCO 3 − can indicate a change in the concentration of media components due to water evaporation or condensation, respectively.…”
Section: Pressure Flow Dissolved Gas and Humidity Measurementsmentioning
confidence: 99%